Yield response and economic impact of variable-rate nitrogen applications in grain sorghum - Riffel, Jarrett Daniel (Kansas State University, 2012)
Variable-rate (VR) nitrogen (N) applications have the potential to improve efficiency of grain sorghum production. Field experiments were conducted in 2010 and 2011 in Stockton and Manhattan, KS. Four VR-N prescriptions were generated using various combinations of grid soil sampling data, soil electrical conductivity (EC) data, and yield maps, and were compared in the field with a uniform application based on a composite soil sample and whole field average yield goal. Soil EC data were used to create management zones that were individually soil sampled. Prescriptions were applied before planting and grain sorghum was harvested and recorded with a yield monitor in the fall. Grain sorghum yields responded to N at both sites with a higher response in 2010 due to more precipitation during the growing season. At Stockton in both years, greatest yields and returns were realized with prescription 4, a combination of management zone soil data and spatially-variable yield goal, while the smallest yields were realized with prescription 2 based on management zone soil data and field average yield goal. Prescription 5, which used grid-soil sampling and a spatially-variable yield goal, and prescription 2 resulted in the lowest returns in both years. At Manhattan in both years, greatest yields and returns were realized with prescription 3, combining a composite soil sample with spatially-variable yield goal. Prescription 5 was among the lowest returning treatments in both years. At Stockton, there was no correlation between yield and soil EC during the 2010 growing season, however there was a significant correlation between yield and shallow EC during the drier 2011 season. At Manhattan, yield was correlated to deep EC in 2010 and to shallow EC in 2011. Overall, increasing spatial intensity of data to develop the prescriptions did not necessarily result in an increased yield response to the application. Prescriptions that included a variable yield goal component tended to perform better across both sites and years.
Keywords: Variable-rate; Nitrogen application; Agronomy (0285)